2015
DOI: 10.1002/anie.201506475
|View full text |Cite
|
Sign up to set email alerts
|

[Ni(cod)2][Al(ORF)4], a Source for Naked Nickel(I) Chemistry

Abstract: The straightforward synthesis of the cationic, purely organometallic NiI-salt [Ni(cod)2]+[Al(ORF)4]– was realized through a reaction between Ni(cod)2 and Ag[Al(ORF)4]. Crystal structure, EPR, XANES and cyclic voltammetry confirmed the presence of a homoleptic NiI-olefin complex. Weak interactions between the metal centre, the ligands and the anion provide a good starting material for further cationic NiI-chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…The remaining spin density is located partly on the aromatic ligand and on the olefinic carbons of the cod ring. Compared to the nickel spin density calculated for 1 + (90 %), a higher degree of delocalization was calculated for the complexes 2 + – 4 + . The increasing delocalization of spin density in the series from the parent benzene substituted 4 + to the hexamethylated arene in 2 + is somewhat unexpected (+I‐effect of the methyl groups)…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The remaining spin density is located partly on the aromatic ligand and on the olefinic carbons of the cod ring. Compared to the nickel spin density calculated for 1 + (90 %), a higher degree of delocalization was calculated for the complexes 2 + – 4 + . The increasing delocalization of spin density in the series from the parent benzene substituted 4 + to the hexamethylated arene in 2 + is somewhat unexpected (+I‐effect of the methyl groups)…”
Section: Resultsmentioning
confidence: 75%
“…With the Ni I complex salt [Ni(cod) 2 ] + [Al(OR F ) 4 ] – , the straight‐forward access to a new class of weakly ligated, isolated Ni I radical cations was established . Herein we report the facile synthesis of cationic formal 19 VE Ni I arene complexes from this starting material.…”
Section: Introductionmentioning
confidence: 99%
“…Ag[Al(OR F ) 4 ] was prepared as previously described and is commercially available at www.iolitec.de. Synthesis of [Ni(cod) 2 ][Al(OR F ) 4 ] was prepared as reported . Single crystals were measured on a Bruker SMART APEX2 diffractometer with CCD area detector, D8 goniometer and an Incoatec Mo‐Microfocus Source iμS with Mo‐K α radiation ( λ =0.71073 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported on [Ni(cod) 2 ][Al(OR F ) 4 ] (cod=1,5‐cyclooctadiene; R F =C(CF 3 ) 3 ) ( 1 ) as the first structurally characterised cationic homoleptic olefin complex (Figure , centre) . Preliminary investigations about substitution of the cod rings demonstrated that 1 could be an auspicious starting material for further nickel(I) complexes, and inspired us to explore new synthesis strategies to generate normal and low‐coordinate homoleptic phosphine complexes using phosphines with different steric demands.…”
Section: Introductionmentioning
confidence: 99%
“…[318] The related CF 3 -functionalized analogues of the type [HCB 11 -(CF 3 ) n F 11Àn ] À have also been prepared;for derivatives where n = 5o r6 ,t he anions can be oxidized with [NiF 3 ] + in anhydrous HF to form the neutral radical species. [324] Thecatalytically relevant chromium-(I) species [Cr(CO) 4 {(Ph 2 P) 2 N i Pr}][Al(OR F ) 4 ]i sr eadily prepared from the neutral chromium(0) precursor through reaction with Ag[Al(OR F ) 4 ]. [318] In addition to the carborane species above,t he icosahedral closo-dodecaborates of the type [B 12 X 12 ] 2À can also be oxidized to form useful oxidants.T he permethylated and perhydroxylated derivatives (i.e.w here X = Me or OH) [B 12 X 12 ]C À have been prepared by the oxidation of the dianionic precursors with the comparatively mild oxidants, ceric ammonium nitrate and hydrogen peroxide,a nd were even structurally characterized.…”
Section: And [Ph 3 C]-[b(c 6 F 5 ) 4 ]Y Ields the [(Mebp Ms )Zr(ch 2 mentioning
confidence: 99%